2023
DOI: 10.31557/apjcp.2023.24.7.2383
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Cytotoxicity of Quercus Brantii Lindl. Galls on A375 and SK-MEL-3 Human Malignant Melanoma Cell Lines

Bahareh Sadat Yosefsani,
Kamyar Mohajer,
Ali Qobadi
et al.

Abstract: This study aimed to find out the mechanism of cytotoxic effects of galls of Quercus Brantii on A375 and SK-MEL-3 melanoma and AGO-1522 normal human fibroblast cell lines for the first time. Therefore, cell viability and cytotoxic activities were evaluated. Furthermore, ROS formation, lipid peroxidation, and release of cytochrome-c were also assessed. The results revealed that the extract of these galls at a concentration of 0.05 mg/ml significantly (P<0.001) increased cytotoxicity, ROS formation, TBARS formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…A recent survey also explored the cytotoxic effects of galls of Q. brantii. The results showed that the extract at a concentration of 0.05 mg/mL significantly (p < 0.001) increased cytotoxicity, ROS formation, lipid peroxidation, and cytochrome-c release in A375 and SK-MEL-3 melanoma versus AGO-1522 normal human fibroblast cell lines [108].…”
Section: Anticancer Activitymentioning
confidence: 95%
“…A recent survey also explored the cytotoxic effects of galls of Q. brantii. The results showed that the extract at a concentration of 0.05 mg/mL significantly (p < 0.001) increased cytotoxicity, ROS formation, lipid peroxidation, and cytochrome-c release in A375 and SK-MEL-3 melanoma versus AGO-1522 normal human fibroblast cell lines [108].…”
Section: Anticancer Activitymentioning
confidence: 95%
“…Brains were removed after decapitation, and striatum tissue was dissected on ice immediately. The striatum was homogenized for 2 min at 4°C in 1.15% potassium chloride (KCl) to determine the levels of the measurement of malondialdehyde (MDA) (an end-product generated by the decomposition of arachidonic acid and larger PUFAs) described previously (15).…”
Section: Measurement Of Malondialdehyde In the Striatum Tissuementioning
confidence: 99%